THE EFFECT OF CHINA'S TAX REFORMATION ON ENTERPRISES - Feng Yi; Agus Suroso (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2013)
The Central People's Government Administration Council issued and announced “The decision on the harmonization of national tax administration "and" Implement Scheme of National Tax Administration” in 1950, which marked founding of tax system of China. Since 1994, China’s central government has started a reformation of this system and established the State Administration of Taxation, the State taxation bureau, as well as the local taxation bureau. Taxes have been adjusted to adapt to the business. After the reformation, government increases revenue, optimizes the fiscal structure, reduces expenditure, improves the local government’s enthusiasm and positivity in economy, ensures fiscal revenue growth and promotes the sustainable development of national economy. Throughout 35 years since the reform and opening policy, especially in the past several years, every reforms of tax system in China impact enterprises (main sources of tax revenue) deeply. How to optimize the current tax system to improve enterprises is an essential research area.